Results of Dynamic Contrast-Enhanced Ultrasound Correlate With Treatment Outcome in Canine Neoplasia Treated With Electrochemotherapy and Interleukin-12 Plasmid Electrotransfer - Brloznik, Maja; Kranjc Brezar, Simona; Boc, Nina; Knific, Tanja; Cemazar, Maja; Milevoj, Nina; Sersa, Gregor; Tozon, Natasa; Pavlin, Darja (Frontiers in Veterinary Science, 2021)
Electrochemotherapy (ECT) and/or gene electrotransfer of plasmid DNA encoding interleukin-12 (GET pIL-12) are effective treatments for canine cutaneous, subcutaneous and maxillofacial tumors. Despite the clinical efficacy of the combined treatments of ECT and GET, data on parameters that might predict the outcome of the treatments are still lacking. This study aimed to investigate whether dynamic contrast-enhanced ultrasound (DCE-US) results of subcutaneous tumors differ between tumors with complete response (CR) and tumors without complete response (non-CR) in dogs treated with ECT and GET pIL-12. Eight dogs with a total of 12 tumor nodules treated with ECT and GET pIL-12 were included. DCE-US examinations were performed in all animals before and immediately after therapy as well as 8 hours and 1, 3 and 7 days later. Clinical follow-up examinations were performed 7 and 14 days, 1 and 6 months, and 1 year after treatment. Numerous significant differences in DCE-US parameters were noted between tumors with CR and non-CR tumors; perfusion and perfusion heterogeneity were lower in CR tumors than in non-CR tumors. Therefore, studies with larger numbers of patients are needed to investigate whether DCE-US results can be used to predict treatment outcomes and to make effective decisions about the need for repeated therapy or different treatment combinations in individual patients.